Music in Belgium : contemporary belgian composres - Belgian Center for Music Documentation (CeBeDem) (Brussels : Manteau, 1964)
Bibliotheek Camille Huysmans
Het "Centre de Documentation Musicale" (CeBeDeM), non profit organisatie, gesticht door Sara Huysmans in 1951
Engels
Monografie
Keywords: komponisten; België